Membrane attack complexes, endothelial cell activation, and direct allorecognition - Song, Guiyu; Wang, Shaoxun; Barkestani, Mahsa Nouri; Mullan, Clancy; Fan, Matthew; Jiang, Bo; Jiang, Quan; Li, Xue; Jane-wit, Dan (Frontiers in Immunology, 2022)
Endothelial cells (ECs) form a critical immune interface regulating both the activation and trafficking of alloreactive T cells. In the setting of solid organ transplantation, donor-derived ECs represent sites where alloreactive T cells encounter major and minor tissue-derived alloantigens. During this initial encounter, ECs may formatively modulate effector responses of these T cells through expression of inflammatory mediators. Direct allorecognition is a process whereby recipient T cells recognize alloantigen in the context of donor EC-derived HLA molecules. Direct alloresponses are strongly modulated by human ECs and are galvanized by EC-derived inflammatory mediators. Complement are immune proteins that mark damaged or foreign surfaces for immune cell activation. Following labeling by natural IgM during ischemia reperfusion injury (IRI) or IgG during antibody-mediated rejection (ABMR), the complement cascade is terminally activated in the vicinity of donor-derived ECs to locally generate the solid-phase inflammatory mediator, the membrane attack complex (MAC). Via upregulation of leukocyte adhesion molecules, costimulatory molecules, and cytokine trans-presentation, MAC strengthen EC:T cell direct alloresponses and qualitatively shape the alloimmune T cell response. These processes together promote T cell-mediated inflammation during solid organ transplant rejection. In this review we describe molecular pathways downstream of IgM- and IgG-mediated MAC assembly on ECs in the setting of IRI and ABMR of tissue allografts, respectively. We describe work demonstrating that MAC deposition on ECs generates ‘signaling endosomes’ that sequester and post-translationally enhance the stability of inflammatory signaling molecules to promote EC activation, a process potentiating EC-mediated direct allorecognition. Additionally, with consideration to first-in-human xenotransplantation procedures, we describe clinical therapeutics based on inhibition of the complement pathway. The complement cascade critically mediates EC activation and improved understanding of relevant effector pathways will uncover druggable targets to obviate dysregulated alloimmune T cell infiltration into tissue allografts.